Reversible Disorder in a Room Temperature Ferromagnet. (23rd January 2014) - Tomarken, Spencer L.; Silevitch, Daniel M.; Aeppli, Gabriel; Brinkman, Braden A.W.; Xu, Jian; Dahmen, Karin A.; Rosenbaum, Thomas F.
<x xml:space="preserve">Abstract</x> Random magnetic fields, varying from site to site in a magnetic material, are a form of disorder that can determine the local architecture and stability of the magnetic state. In a ferromagnet, the application of an external magnetic field can amplify the effects of the internal random fields and, in principle, harden a magnetic domain, without changing temperature and only for as long as the external field is present. Here, the rare‐earth compound Nd2Fe14B, formed with a granular morphology of random‐packed, elongated grains, is an experimental realization of the Random Field Ising Model in a room temperature ferromagnet. The application of magnetic fields transverse to the easy axis tunes the coupling between the structural disorder and the magnetic pinning properties. This material both illuminates the intricacies of tunable disorder and serves as a guidepost along the way to developing increased‐density magnetic storage media.